Signature verification system using support vector machine - Fauziyah, Salehuddin; Azlina , Othman (2009)
This paper highlights the development of online signature verification system using Support Vector Machine (SVM) and VBTablet 2.0 to verify the input signature by comparing database. This may take place by signing directly on to a digitizing tablet by using stylus which is connected to the Universal Serial Bus (USB) port of computer. Owing to the fact that each individual has its own way of presenting his/her signatures on paper, there is a certain level of complexity like the way of holding the stylus, the strokes used in the signing and the amount of time/pressure put on paper which are involved in this verification system. The general on-line verification procedures are preprocessing, features extraction, detail matching and post processing. The common verification algorithm is one of the Global Feature Vector Machine called Support Vector Machine (SVM). The signature is characterized as pen-strokes consisting x-y coordinates and the data will be stored in the signature database in the form of a txt.file.